PENGARUH JAHE TERHADAP AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK MINUMAN EKSTRAK JAGUNG UNGU (Zea mays L.) - Inka Condro Istia; Mohamma Jusuf Randi; Nurwati Nurwati (Journal of Food Technology and Agroindustry, 2023)
One of the cultivable food crops, corn also serves a strategic purpose and has economic worth. Corn, as the primary source of carbs, is utilized as a rice alternative. Beverage goods are one alternative that can be made from corn. Anthocyanins found in purple corn work as antioxidants to stop atherosclerosis in the body. One sort of spice that offers numerous health advantages is ginger. Antioxidants are substances that can limit oxidation reactions by attaching to free radicals and highly reactive molecules. Antioxidants in food can minimize food spoiling processes, free radical oxidation, slow down the oxidation of lipids and oils, increase shelf life in the food sector, increase the storage of fat contained in food and prevent sensor and nutritional quality degradation. This study used the DPPH method (1,1-diphenyl-2,-picrylhydrazyl) which is a purple compound that will turn yellow when reacted with antioxidant activity and used a completely randomized design (CRD) method in the form of a single factor ratio of corn: ginger extract ( 100 g : 2 g, 3 g, 4 g, and 5 g) using 5 treatments and 3 replications. The organoleptic test used is the hedonic test, namely the level of preference test for the taste, texture, color, color of the purple corn extract drink. The score used is 1 – 5 (very dislike, dislike, somewhat like, like, and like very much). The data obtained were then analyzed and processed using SPSS with one way ANOVA. The purpose of this study was to determine the antioxidant activity and the panelists' preference level of purple corn extract drink.